Multicultural psychology - Nagayama Hall, Gordon C., ....- (New York : Routledge, 2018)
Multicultural Psychology introduces students to the myriad ways in which multicultural issues affect our understanding of, and research in, a wide range of domains including biological, developmental, social, and clinical psychological science. It provides in-depth coverage of the largest groups of color in the United States: African Americans, Latinx Americans, Asian Pacific Americans, and Native Americans. Students will gain an understanding of how race, ethnicity, and culture shape their own behavior, beliefs, interactions, and expectations, and those of the people around them. New to this edition: -New chapters on Clinical Psychology and Racial/Ethnic Identity and Acculturation -Greater focus on study of intersectional identities -Incorporates up-to-date research from a rapidly growing literature -Expanded coverage of qualitative research methods -Information about supplemental blog and video resources -Companion Website where students will find review questions and resource links, and instructors will find PowerPoint slides and discussion questions